Artemisinin derivative FO-ARS-123 as a novel VEGFR2 inhibitor suppresses angiogenesis, cell migration, and invasion. (25th September 2022) - Lu, Xiaohua; Elbadawi, Mohamed; Blatt, Sebastian; Saeed, Mohamed E.M.; Xiao, Xiaolin; Ma, Xiao; Fleischer, Edmond; Kämmerer, Peer W.; Efferth, Thomas
Abstract: Anti-angiogenesis targeting vascular endothelial growth factor receptor 2 (VEGFR2) has been considered an important strategy for cancer therapy. VEGFR2 inhibitors targeting tumor angiogenic pathways have been widely used in clinical cancer treatment. However, inherent or acquired resistance to anti-angiogenic drugs may occur and thus limit their clinical application. New VEGFR2 inhibitors are still highly demanded. The aim of this study was to investigate VEGFR2-targeted artemisinin (ARS)-type compounds for cancer treatment. Here, we reported the ARS derivative FO-ARS-123 as a novel VEGFR2 inhibitor, which displayed potent binding activity with VEGFR2 in in silico by molecular docking (pKi, 0.40 ± 0.31 nM) and in vitro by microscale thermophoresis (Kd, 1.325 ± 0.055 μM). In addition, compound FO-ARS-123 displayed a strong inhibition on cell proliferation of a broad range of cancer cells as well as suppressed cell migration and invasion. Remarkably, FO-ARS-123 exerted profound anti-angiogenesis effects in the in vitro tube formation assay and in vivo CAM assay. These results suggest that FO-ARS-123 might be a novel and promising anti-angiogenesis agent for cancer treatment. Graphical abstract: Image 1 Highlights: VEGFR2-targeted FO-ARS-123 is screened out from 416 Artemisinin (ARS)-type derivatives. FO-ARS-123 exhibits profound cytotoxicity on a panel of eight cancer cell lines. FO-ARS-123 suppresses cell migration and invasion, and induces cell apoptosis. FO-ARS-123 exerts favorable anti-angiogenesis effects in tube formation assay in vitro and CAM assay in vivo.